La crítica de Etchemendy al formalismo - Gariazzo, Matías (2011)
“Etchemendy’s Critique to Formalism”. John Etchemendy claims that,given the failure of the Tarskian intuitive notion of logical consequence, there isno reason to consider formality as a necessary condition for this relationship.This paper critiques this argument. First, it seeks to show that Etchemendy’scritique to Tarskian analysis assumes two requisites of elucidatory success thatcannot be held together reasonably. Secondly, it shows that, once the previousassumption is rejected, two arguments in favour of the extensional adequacyof the former argument actually support formalism. Finally, this paper reviewssome well known pragmatic considerations in favour of formalism.